Medicine's Duty to Treat PANDEMIC ILLNESS: SOLIDARITY AND VULNERABILITY - Brody, Howard (The Hastings Center report, 2009)
Most accounts of why physicians have a duty to treat patients during a pandemic look to the special ethical standards of the medical profession. An adequate account must be deeper and broader: it must set the professional duty alongside other individual commitments and broader social values.